Acidosis Differentially Modulates Inactivation in NaV1.2, NaV1.4, and NaV1.5 Channels - Vilin, Yury Y.; Peters, Colin H.; Ruben, Peter (Frontiers in Pharmacology, 2012)
NaV channels play a crucial role in neuronal and muscle excitability. Using whole-cell recordings we studied effects of low extracellular pH on the biophysical properties of NaV1.2, NaV1.4, and NaV1.5, expressed in cultured mammalian cells. Low pH produced different effects on different channel subtypes. Whereas NaV1.4 exhibited very low sensitivity to acidosis, primarily limited to partial block of macroscopic currents, the effects of low pH on gating in NaV1.2 and NaV1.5 were profound. In NaV1.2 low pH reduced apparent valence of steady-state fast inactivation, shifted the τ(V) to depolarizing potentials and decreased channels availability during onset to slow and use-dependent inactivation. In contrast, low pH delayed open-state inactivation in NaV1.5, right-shifted the voltage-dependence of window current, and increased channel availability during onset to slow and use-dependent inactivation. These results suggest that protons affect channel availability in an isoform-specific manner. A computer model incorporating these results demonstrates their effects on membrane excitability.